Basketball : a guide for players and fans - Williams, Heather, 1974- (2020)
"Basketball : A Guide for Players and Fans gives young readers a courtside look at one of the world's most popular sports. Readers will find easy-to-read explanations of basketball's beginnings, basic rules and strategies, and how they can suit up and get on the court. This book features colorful photos, fun facts, and informative sidebars, and kids who love basketball won't want to stop reading until they're ready for tip-off!"--
Ages: 8 to 9.
Grades: K to grade 3.
Keywords: Basketball -- Juvenile literature; Basketball